Arctigenin Suppresses Melanoma via Mitophagy Activation In vitro and Enhances Dacarbazine Sensitivity In vivo - Jiang, Ling; Lu, Yang; Zhao, Hongyan; He, Weiyang (Current Cancer Drug Targets, 2025)
ObjectiveThis study aimed to investigate the effect and mechanism of arctigenin (ARG) on the sensitization of dacarbazine (DTIC) via the regulation of mitophagy.MethodsIn vitro experiments were conducted to explore the effects of ARG on the biological behavior of melanoma cells, mitochondrial autophagy mediated by PINK1/Parkin, and the role of reactive oxygen species (ROS)-mitochondrial autophagy in the regulation of the biological behavior of melanoma cells by an ROS quenching agent, a mitochondrial autophagy inhibitor, and an activator. The effects of ARG and dacarbazine in nude mice were assessed.ResultsCCK8 assays revealed that ARG inhibited the proliferation of the human melanoma cell lines A375 and SK-MEL-2. The observation of submicroscopic structures demonstrated mitochondrial damage. Flow cytometry further verified that ARG induced apoptosis. Western blot analysis revealed that the protein expression levels of cleaved caspase 3 and Bax increased, whereas that of Bcl-2 decreased. In addition, ARG increased ROS levels. LC3II/I, PINK1, and Parkin were increased. ARG-induced apoptosis was related to increased mitochondrial oxidative stress and promoted the occurrence of mitochondrial autophagy. After the addition of the autophagy inhibitor Mdivi-1 or the ROS quencher N-acetylcysteine (NAC), the antiproliferative effect of ARG was markedly attenuated. The expression levels of PINK1, Parkin, LC3II/I, cleaved caspase 3, and Bax were increased, whereas that of Bcl-2 was decreased. The formation of mitochondrial autophagosomes was observed by transmission electron microscopy. ARG inhibited the proliferation and induced the apoptosis of melanoma cells in vivo.ConclusionAutophagy-mediated cell apoptosis was activated through the PINK1/Parkin pathway by ARG, effectively inhibiting the proliferation of human melanoma cells.
Keywords: dacarbazine